The effects of UMA (Unified Model of Aesthetics) and CM (Categorical-Motivation Model) in the application of aesthetic preferences for clothing products - Qianhui, Ren; Yahaya, Mohd Faiz; Lichen, Tai; Wu, Qi; Hui, Chen (Human Resource Management Academic Research Society, 2024)
Aesthetic preferences for artefacts are affected by many factors, such as perceptual factors, cognitive factors, and social factors. Currently, there are two models (the UMA model and the CM model) that provide theoretical support for aesthetic preferences for artefacts. However, most previous studies have focused on testing the cognitive level of the UMA model, and there is still a lack of complete testing of the three levels of the UMA model. Furthermore, categorization motivation models divide artefacts into “rich” and “poor” categories, with different categories having different impacts at the perceptual, cognitive, and social levels. This study aims to examine people's aesthetic preferences for clothing products in mainland China, using the UMA model and CM model as the theoretical basis to study the aesthetic preferences of different categories of clothing products in terms of perception, cognition and society. This study is the first to completely test the three-level relationship of the UMA model through clothing products and combines the product classification of the CM model to test people's aesthetic preferences from the perceptual, cognitive and social levels.